Incarcerated Amyand hernia with necrosis of the appendix and cecum - Renato Queiroga de Almeida; Aline Zara; Daniela Ferreira; Fernando Schulz; Jaques Waisberg (Elsevier, 2021)
Introduction: Presence of vermiform appendix (inflamed or not) within a hernia sac is called Amyand hernia. It is a rare disease, occurring about 1% of inguinal hernia patients. Commonly the diagnosis occurs intraoperatively. Case report: A 7-month-old boy was admitted with abdominal distension, vomiting and non-stooling for the past 3 days. Examination revealed a painful abdomen on palpation, scrotal erythema and irreducible mass on right inguinoscrotal region. A plain abdominal X-ray showed dilated colon and small bowel loops. At surgery, we performed laparotomy and was founded cecum and appendix inside the hernia sac, with signs of necrosis. Due to extension of ischemia, the cecal appendix, cecum, and terminal ileum were resected, and an end-to-end ileo ascending colon anastomosis was performed. The hernia sac was closed with a right inguinotomy. Discussion: Amyand hernia is a rare disease, occurring in about 1% of adult herniotomies. In children is much less uncommon, estimated in 0,07-0,28%, and the presence of an inflamed vermiform appendix is related as 0,08%. There are several clinical manifestations of Amyand hernia: reducible or incarcerated hernia within non-inflamed appendix or inflamed appendix to systemic signs of sepsis. Pre-operative imaging studies (such as ultrasonography or computed tomography) can be useful. The diagnosis generally occurs intraoperatively. Appendectomy in Amyand hernia remains controversial. Conclusion: AH is usually diagnosed as an incarcerated/strangulated right inguinal hernia and should be considered in the differential diagnosis of incarcerated/strangulated in neonates and infants. Adequate treatment is an urgent surgical exploration of the inguinal region and laparotomy, if necessary. The surgical approach in the presence of suspected ischemia, necrosis, or perforation of the structures placed inside the hernia sac may prevent the need for intestinal resection.